Sardar Vallabhbhai Patel: a biography - Patel, Sardar Vallabhbhai (New Delhi Pigeon Books, 2019)
"Sardar Vallabhbhai Patel was an Indian barrister and statesman, one of the leaders of the Indian National Congress and one of the founding fathers of the Republic of India. He was a social leader who played a leading role in the country struggle for independence and guided its integration into a United, independent nation. In India and elsewhere, he was often addressed as Sardar, which means chief in Hindi, Urdu and Persian. Sardar Patel was raised in the countryside of Gujarat. Patel was employed in successful practice as a lawyer. Patel subsequently organised peasants from Kheda, Borsad, and bardoli in Gujarat in non-violent Civil disobedience against oppressive policies imposed by the British Raj; in this role, he became one of the most influential leaders in Gujarat. He rose to the leadership of the Indian National Congress and was at the forefront of rebellions and political events, organising the party for elections in 1934 and 1937, and promoting the quit India movement.".
Keywords: Biography; Sardar Vallabhbhai Patel